Residential solar water heating: California adopters and their experiences. (June 2021) - Sanguinetti, Angela; Outcault, Sarah; Alston-Stepnitz, Eli; Moezzi, Mithra; Ingle, Aaron
Abstract: Solar water heating provides domestic hot water with lower greenhouse gas emissions compared to more typical natural-gas water heating. Solar water heating has a long history, particularly in places where the climate is favorable, such as California where state-backed incentive programs have been successful in creating small bursts of adoption. However, widespread adoption of solar water heating has not occurred in California despite these conditions. This research surveyed 227 single-family households with solar water heating across the state of California to understand their motivations and experiences, and draw implications regarding barriers to adoption. The survey explored households' experiences across five stages of adoption, as outlined in Rogers' Diffusion of Innovation theory: Knowledge, Persuasion, Decision, Implementation, and Confirmation. Findings revealed challenges at each stage. Most notably, prevalent disappointment in lower-than-expected energy and bill savings (31%) and high rates of technical problems (41%) appear to be the most significant issues. Highlights: This research surveyed 227 California households with solar water heating. Findings describe adopters' motivations and experiences with solar water heating. High installation cost was a prevalent concern despite generous incentives. Adopters often had difficulty finding a competent or trustworthy installer. Technical problems and disappointment in savings were markedly prevalent.